2011
DOI: 10.1007/s00381-011-1527-5
|View full text |Cite
|
Sign up to set email alerts
|

Time trends and age-related etiologies of pediatric hydrocephalus: results of a groupwise analysis in a clinical cohort

Abstract: Despite recent advancements, hydrocephalus is still associated with high rate of shunt failure and mortality. Factors associated with poor outcome include younger age group and etiology of hydrocephalus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…Other demographic factors like sex, age and co-morbid conditions did not influence the frequency of shunt failure in this study. A predominance of male patients (64.2%) was noted in our study and is in accordance with a previous report from our own hospital (38). This trend has also been noted in other studies from the developing world (12,24).…”
Section: █ Discussionsupporting
confidence: 93%
“…Other demographic factors like sex, age and co-morbid conditions did not influence the frequency of shunt failure in this study. A predominance of male patients (64.2%) was noted in our study and is in accordance with a previous report from our own hospital (38). This trend has also been noted in other studies from the developing world (12,24).…”
Section: █ Discussionsupporting
confidence: 93%
“…3,6,13,22 In addition to the overall effect in an unselected group of pediatric patients on whom we report, there was a significant improvement with respect to infection rates in the 0-6-month age group. This group of patients, particularly those with posthemorrhagic hydrocephalus, appear to be at greater risk of shunt-related morbidity and mortality, 19,27 and it is encouraging that in this study AIS tubing appears to be effective in improving outcomes in this group.…”
Section: Discussionmentioning
confidence: 67%
“…We believe that this approach would help especially in resource-challenged health care systems and developing countries such as Pakistan, where CH is the most common neurologic congenital defect and also the most common reason for neurosurgical intervention in pediatric patients. 9,10 These children, after surgery and initial screening for possible complications, are critically exposed to economic and social handicaps due to a lack of awareness programs and good social rehabilitation centers, increasing the probability of suboptimal health outcomes and QOL.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 However, CH involves long-term follow-up and is associated with numerous possible complications. Rashid et al 10 reported a poor surgical outcome in children treated for pediatric hydrocephalus in Pakistan. Considering the prevalent poverty as well as the lack of well-developed social rehabilitation Key words -Congenital -Hydrocephalus -Hydrocephalus Outcome Questionnaire (HOQ) -Quality of life (QOL)…”
Section: Introductionmentioning
confidence: 99%